1995
DOI: 10.1074/jbc.270.44.26639
|View full text |Cite
|
Sign up to set email alerts
|

Partial Inhibition of Multidrug Resistance by Safingol Is Independent of Modulation of P-glycoprotein Substrate Activities and Correlated with Inhibition of Protein Kinase C

Abstract: Safingol is a lysosphingolipid protein kinase C (PKC) inhibitor that competitively interacts at the regulatory phorbol binding domain of PKC. We investigated the effects of safingol on antineoplastic drug sensitivity and PKC activity of MCF-7 tumor cell lines. Safingol treatment of 32 P-labeled MCF-7 WT and MCF-7 DOX R cells inhibited phosphorylation of the myristoylated alaninerich protein kinase C substrate in both cell lines, suggesting inhibition of cellular PKC. However, only in MCF-7 DOX R cells did safi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 58 publications
0
57
3
Order By: Relevance
“…68 An analog of sphingosine, L-threo-dihydrosphingosine (known as safingol), which also acts as a sphingosine kinase inhibitor, enhanced doxorubicin accumulation and sensitivity of MCF-7 drug-resistant cells. 69 Because DMS and L-threodihydrosphingosine induce apoptosis regardless of P-glycoprotein expression, they may provide a new strategy for the treatment of anticancer drug-resistant cancers. Indeed, in pilot clinical phase I trials with safingol, which also potentiated the tumor-inhibiting effect of doxorubicin in tumor-bearing animals, it was found that safingol can be given safely with doxorubicin.…”
Section: S1p In Hematopoietic Malignancies: Potential Use Of Sphingosmentioning
confidence: 99%
“…68 An analog of sphingosine, L-threo-dihydrosphingosine (known as safingol), which also acts as a sphingosine kinase inhibitor, enhanced doxorubicin accumulation and sensitivity of MCF-7 drug-resistant cells. 69 Because DMS and L-threodihydrosphingosine induce apoptosis regardless of P-glycoprotein expression, they may provide a new strategy for the treatment of anticancer drug-resistant cancers. Indeed, in pilot clinical phase I trials with safingol, which also potentiated the tumor-inhibiting effect of doxorubicin in tumor-bearing animals, it was found that safingol can be given safely with doxorubicin.…”
Section: S1p In Hematopoietic Malignancies: Potential Use Of Sphingosmentioning
confidence: 99%
“…Pretreatment with calphostin C was carried out under dim light in the incubator. For treatment with L-threo-dihydrosphingosine (safingol), ethanol stock solution of safingol (Sigma) was diluted into α-MEM containing 1 mM BSA, sonicated briefly, and then incubated at room temperature for 1 h to form complexes as described 39 . The cells were then treated with either 10 μM safingol or vehicle for 4-6 h before recording.…”
Section: Cell Cultures and Cdna Deliverymentioning
confidence: 99%
“…5a,c). In contrast, calphostin C and safingol, which act on the diacylglycerol binding site 38,39 , reduced the sensitivity to Oxo-M (Fig. 5a,b).…”
mentioning
confidence: 99%
“…PKC activators also increased drug accumulation and decreased drug sensitivity in MCF-7/Adr (Fine et al, 1988) and KM12L4a cells (Dong et al, 1991), and induced MDRJ gene expression in normal human lymphocytes (Chaudhary and Roninson, 1992). Conversely, a variety of PKC inhibitors, such as staurosporine (Sato et al, 1990), the staurosporine analogues CGP 41251 (Utz et al, 1994; Budworth et al, 1996) and GF 109203X , calphostin C (Bates et al, 1993) and safingol (Sachs et al, 1995), reversed P-gp-mediated mdr. However, reversal of drug resistance caused by staurosporine analogues is probably associated with direct interaction with P-gp rather than with PKC inhibition (Smith and Zilfou, 1995;Gekeler et al, 1996;Goodfellow et al, 1996;Budworth et al, 1996).…”
mentioning
confidence: 99%